THE IDENTIFICATION OF BORNEO MALAY MANUSCRIPTS IN KUALA LUMPUR, MALAYSIA: A PRELIMINARY STUDY - Pramono, Pramono; Mohd Dasuki Wan Hasbullah, Wan; Salman Herbowo, Ahmad (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2023)
ABSTRACT Borneo manuscripts make up parts of intellectual heritage, critical in the cultural and historical construct of the Malay World. Additional information and knowledge regarding the whereabouts of Borneo manuscripts, especially the collection kept at document centers outside Borneo, is considered necessary in efforts to enhance source materials based on written texts. This study investigates a number of Borneo Malay manuscripts, which are kept at two document centers in Kuala Lumpur, Malaysia: Perpustakaan Negara Malaysia and Dewan Bahasa dan Pustaka. The Borneo manuscripts in this study are limited from 1987 to 2018, which are then categorized by actual numbers, type of manuscripts and titles, genres, and sub-genres. 155 Borneo manuscripts were identified in this study, classified into 8 genres and 21 sub-genres. These manuscripts are representative of writings at different points in time in the 10 regions of Borneo. This study contributes to mapping Borneo manuscripts as a reference for future researchers. Keywords: Borneo Manuscripts, Catalogue Studies, Manuscript Identification, Genres Classification. ABSTRAK Manuskrip Borneo merupakan bagian dari warisan intelektual, kritis dalam konstruksi budaya dan sejarah Dunia Melayu. Informasi dan pengetahuan tambahan mengenai keberadaan naskah-naskah Kalimantan, khususnya koleksi yang disimpan di pusat-pusat dokumen di luar Kalimantan, dianggap penting dalam upaya peningkatan bahan sumber berdasarkan naskah-naskah tertulis. Studi ini menyelidiki sejumlah manuskrip Melayu Kalimantan yang disimpan di dua pusat dokumen di Kuala Lumpur, Malaysia yaitu: Perpustakaan Negara Malaysia dan Dewan Bahasa dan Pustaka. Naskah Kalimantan dalam penelitian ini dibatasi dari tahun 1987 hingga 2018, yang kemudian dikategorikan berdasarkan jumlah aktual, jenis naskah dan judul, genre dan sub-genre. 155 manuskrip Kalimantan teridentifikasi dalam penelitian ini, diklasifikasikan ke dalam 8 genre dan 21 sub-genre. Manuskrip-manuskrip ini mewakili tulisan-tulisan pada berbagai titik waktu di 10 wilayah Kalimantan. Studi ini berkontribusi pada pemetaan naskah Kalimantan sebagai referensi bagi peneliti selanjutnya. Kata Kunci: Manuskrip Borneo, Studi Katalog, Identifikasi Manuskrip, Klasifikasi Genre